Desempenho,composição e utilização de nutrientes no híbrido (cachara x jandiá) alimentados com variações de carboidratos e lipídio na dieta - Bernardes, Célio Luiz (2012)
This study evaluated the influence of different carbohydrate/lipid ratios (CHO:L) in the diet of hybrid catfishes, carnivorous Pseudoplastitoma reticulatum x omnivorous Leiarius marmoratus, on the performance, body composition and nutrient utilization. Four isoproteic diets were formulated containing 43% crude protein, with increasing levels of lipids with CHO: diet I, 1.3; diet II, 1.1; diet III, 0.9; diet IV, 0.8. The fishes were fed at 5% of the living body weight (LBW) for the triplicate groups of 6 fishes (18 ± 1.5 g) during 8 weeks. Although the final weight and the absolute weight gain decreased with the increase of lipids in the diet, no significant difference was found in the ration daily consumption (DC) between the treatments. In addition, the viscerosomatic index (VSI) and the hepatosomatic index (HIS) showed no statistic difference between the dietary treatments. Protein efficiency retention (PER), lipid efficiency retention (LER) and protein gain (PG) were higher in the 1.3 CHO:L group, but no significant difference was found between the 0.9 and 0.8 CHO:L groups. In conclusion, high CHO:L ratios around 1.3 produced great benefit due to the best growth performance in the studied hybrid model.